The Interpreting Ability on Science Kinematics Graphs of Senior High School Students in South Sulawesi, Indonesia (Jurnal Pendidikan IPA Indonesia, 2020)
This research was a descriptive case study. The purpose of this research was to describe the student’s ability to interpret the kinematics graph. The subjects of the study were 347 students of class XI science in the even semester of 2018/2019 in Luwu Raya, South Sulawesi Province, Indonesia. The research data were obtained from multiple-choice test results using instruments adapted from Test of Understanding Graph – Kinematics 2.6 and the results of in-depth interviews to find out the reasons learners choose answers and casual factors. The results of the study based on descriptive data analysis were 90 students or 25.94% in the low category, and 257 students or 74.06% were in the very low category. These results indicate the ability to interpret the graphs of students were still low, with the average achievement in answering questions on each of the highest indicators was 20.99 % on indicators identifying graphs based on the description. While the lowest average achievement was11.91%, which is the indicator to identify the graph that has a different variable. Base on the qualitative data analysis, the results are students had difficulties in solving the test, as follows: a) the difficulty in distinguishing symbol of the variables on the graph, b) the difficulty in determining the formula for solving test in graphical form, c) to determine when the curve on the graph v-t decreases then the object will move with speed slowed. The factors causing these difficulties are because students did not understand deeply about how to read graphs, how to solve test in graphical form, and did not understand the formula used to solve the test.